Prinsip Penyelesain Beberapa Isu Bioetika Dalam Bahasa Fiqih - Rohma, Alifatur; Pratiwi, Dwi Anisa; Hakim, Luqman Taufiqul (Maliki Interdisciplinary Journal, 2025)
A B S T R A C T The rapid advancement of science and technology in the biomedical field has greatly benefited human life but has also raised various ethical issues that require guidance from Islamic jurisprudence (fiqh). This study aims to examine the principles of Islamic fiqh in addressing modern bioethical challenges and to explore the role of fiqh language as a moral framework in responding to developments in medical technology. The research employs a qualitative method with a library research approach, drawing from classical and contemporary fiqh texts, religious fatwas, and recent scientific studies. The findings reveal that the maqāṣid al-syarī‘ah (objectives of Islamic law)—protection of religion, life, intellect, lineage, and property—form the foundation for ethical evaluation in medical practices. Principles such as darūrah (necessity), maslahah and mafsadah (benefit and harm), and the legal maxim al-ḍarūrāt tubīḥ al-maḥẓūrāt (necessities permit prohibitions) are applied to issues such as organ transplantation, in vitro fertilization, euthanasia, and genetic engineering. Furthermore, the language of fiqh functions as an ethical and epistemological guide that bridges religious values and scientific progress, fostering a balanced perspective between morality and innovation. Therefore, the integration of fiqh and modern bioethics is essential to build a holistic, humane, and spiritually grounded framework for contemporary medical ethics.